2021
DOI: 10.1038/s41598-021-94645-z
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evolution of Mycobacterium on agar plates for analysis of resistance acquisition and drug sensitivity profiles

Abstract: Drug-resistant tuberculosis (TB) is a growing public health problem. There is an urgent need for information regarding cross-resistance and collateral sensitivity relationships among drugs and the genetic determinants of anti-TB drug resistance for developing strategies to suppress the emergence of drug-resistant pathogens. To identify mutations that confer resistance to anti-TB drugs in Mycobacterium species, we performed the laboratory evolution of nonpathogenic Mycobacterium smegmatis, which is closely rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
2
15
0
1
Order By: Relevance
“…In conclusion, our study outputs imply that mycobacterial resistance to beta-lactams may not be as simplistic as once thought. Confirmation of mutations in Rv2864c and upstream MSMEG_6319 in mutants isolated with meropenem, corroborated previous descriptions of the involvement of the Msm gene in resistance to this carbapenem ( Maeda et al, 2021 ). This is also in agreement with our previous description that Mtb clinical strains with a mutation in LpqK, another lipoprotein with similarity to PBPs and D,D-carboxypeptidases, show reduced meropenem MICs ( Olivença et al, 2022 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In conclusion, our study outputs imply that mycobacterial resistance to beta-lactams may not be as simplistic as once thought. Confirmation of mutations in Rv2864c and upstream MSMEG_6319 in mutants isolated with meropenem, corroborated previous descriptions of the involvement of the Msm gene in resistance to this carbapenem ( Maeda et al, 2021 ). This is also in agreement with our previous description that Mtb clinical strains with a mutation in LpqK, another lipoprotein with similarity to PBPs and D,D-carboxypeptidases, show reduced meropenem MICs ( Olivença et al, 2022 ).…”
Section: Discussionsupporting
confidence: 87%
“…Rv2864c is a putative high-molecular-mass PBP with a lipoprotein motif, recently shown to be relatively resistant to all beta-lactam subclasses when compared to other well-known PBPs ( Kumar et al, 2022 ). The mutation in the putative promoter region of MSMEG_6319 (AT701_RS30910) has been previously described in meropenem-resistant Msm mutants ( Maeda et al, 2021 ). The detection of a mutation in Rv2864c in the meropenem-resistant Mtb isolates in our study is in accordance with these observations and further supported by reports of increased cefotaxime sensitivity in a Mtb mutant generated through Rv2864c disruption and by CRISPR interference studies on Mycobacterium abscessus orthologue gene MAB_3167c ( Wivagg et al, 2016 ; Akusobi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the method of agar-based selection for laboratory evolution against antibiotics ( Maeda et al., 2021 ) or induced by high-concentration drugs ( Zhao et al., 2014 ), the strategy of a continuous drug concentration gradient can better simulate the accumulation of drugs in the human body. Determination of the MIC value of 14 anti-TB drugs showed that laboratory-induced mono-EMB drug-resistant strains were successfully obtained ( Supplementary Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…BrkB também deve atuar nos mecanismos de aderência e invasão desta bactéria nas células hospedeiras. Este domínio também pode ser encontrado em outras bactérias como Escherichia coli (Ezraty et al, 2005) e Mycobacterium tuberculosis (Maeda et al, 2021). Foi possível identificar apenas uma proteína com domínio Virul_fac_BrkB na L. interrogans e L. biflexa, sendo caracterizadas como proteínas ortólogas e, posteriormente, classificadas como proteínas pouco conservadas.…”
Section: Proteína Com Domínio Virul_fac_brkbunclassified